Dental age assesment in patients with hypodontia using Willems's method - Sukmasari, Susi; Ardini, Yunita Dewi; Cheong, Joo Ming (2013)
Objective: To compare the dental age and chronological age of permanent teeth in children with hypodontia. Materials and methods: This was a cross-sectional study based on Orthopantomograms (OPGs) sample of children and adolescents of known age (6-14 years old), attended Dental Clinic of Paediatric Dentistry and Orthodontics at IIUM, Kuantan Campus in Pahang, Malaysia, from 2009 to 2012. Out of 727 OPGs, 38 OPGs with hypodontia which fulfilled the inclusion criteria were selected. The OPG machine used was Planmeca ProMax 3D, which provides detailed high resolution of 3 lp/mm image without artefacts. The exposure time was 12 seconds with a magnification factor of 1.45. Data regarding hypodontia was collected. Assessments were performed using Planmeca Romexis 2.8.O.R software. Dental age of all permanent teeth on the left mandible was assessed using Willems's method (4) from the OPGs. Chronological age was measured from birth to a given date when OPG was taken. The difference between dental and chronological age was analysed using t-test. Results: Dental age of permanent teeth in both boys and girls was lower than the chronological age. Dental age of permanent teeth in boys was lower than the dental age of permanent teeth in girls. Dental age in children with hypodontia was significantly lower compared to the chronological age (p=0.000). Conclusion: Dental age of permanent teeth in children with hypodontia was lower than chronological age. Dentist should be aware about hypodontia since it is the most common dental anomalies.